Margin Sampling and Survival Outcomes in Oral Cavity and p16-Positive Oropharyngeal Squamous Cell Carcinoma. Issue 3 (September 2022) - MacKay, Colin; Turner, Brooke; Bullock, Martin; Taylor, S. Mark; Trites, Jonathan; Corsten, Martin; Geldenhuys, Laurette; Rigby, Matthew H.
Objective: To compare the association of margin sampling technique on survival outcomes in surgically treated cT1-2 oral cavity and oropharyngeal squamous cell carcinoma. Study Design: A prospective longitudinal cohort study. Setting: Tertiary care academic teaching hospital in Halifax, Nova Scotia. Methods: All cases of surgically treated cT1-2 oral cavity and oropharyngeal cancer undergoing specimen-oriented margin analysis between January 1, 2017, and December 31, 2018 were analyzed. The specimen-oriented cohort was compared with a cohort of patients from January 1, 2009, to December 31, 2014, where a defect-oriented margin sampling protocol was used. Kaplan-Meier survival curves were used to estimate 2-year overall survival, disease-specific survival, local control, and recurrence-free survival rates in oral cavity and p16-positive oropharyngeal squamous cell carcinoma. Cox proportional hazards models were used to assess the effect of margin sampling method on disease-specific survival and local control. Results: There was no significant association between margin sampling technique and 2-year survival outcomes for surgically treated cT1-2 oral cavity and oropharyngeal squamous cell carcinoma. In the multivariate Cox proportional hazard model, the hazard ratio (HR) of specimen-oriented sampling was not significantly different for disease-specific survival (HR, 1.32; 95% CI, 0.3032-5.727; P = .713) or local control (HR, 0.4087; 95% CI, 0.0795-2.099; P = .284). Conclusion: Intraoperative margin sampling method was not associated with a significant change in 2-year survival outcomes. Despite no effect on survival outcomes, implementation of a specimen-oriented sampling method has potential for cost avoidance by decreasing the number of re-resections for positive or close margins.